O kit anti-homofobia e os discursos sobre diversidade sexual - Pamplona, Renata Silva (Universidade Federal de São Carlos, 2012)
With this research the aim is to analyze the different discourses propagated in the Brazilian media, referring to the repercussion of the possibility of the approval of the educational material: the Anti-homophobia kit, produced and developed by MEC / SECADI, based on the project, A Homophobia-free School, between 2008 and 2010. This material is intended to support the educational task in tackling prejudice against sexual diversity and combat homophobia in schools. As methodological option, we will work with Foucaultian Arqueogenealogy, given that this event falls within the domain of knowledge and power. In this sense, it is allied to the understanding that the discourse is complex, transient, mobile, marked by historical relationships and practices that are actually alive within the discourse itself. This cannot be reduced to a set of signs and signifiers; nor is it causal. Before, it is subject to the law of becoming. In this slant, and in the understanding that sexuality is historically produced, functioning as a device of sexuality, we proceed in the first instance to analyses of the following audiovisual materials: Finding Bianca, Probability and Torpedo. Subsequently, we analyze the discourses propagated on the educational material and on sexual diversities. The entire discursive trajectory and its detailed examination offers tools which make it possible to understand the Anti-homophobia kit as a device of power. Thus, as we proceed through the discursive tangle and begin to unravel the minutiae produced by the discourses, it can be seen that these construct themselves in such a manner as to produce truth about sexual diversities, and to engender forms of subjectification of the differences. Specifically, strategies are perceived to purge or make palatable any expression of strangeness concerning: transvestites, transsexuals, lesbians, gays, bisexuals or transgender individuals. The Anti-homophobia kit resource reaffirms traditional models of heteronormativity, even though the discourses subtly construct themselves in defense of the subjects one wishes to normalize.
Keywords: Educação; Diversidade sexual; Homofobia; Normalização; Dispositivo (Filosofia); Kit anti-homofobia; Anti-homophobia kit; sexual diversity; resource; normalization; CIENCIAS HUMANAS::EDUCACAO